Ingestion of Artemisia argyit essential oil combats Salmonella pullorum infections by altering gut microbiota composition in chicks - Linlin Ding; Kaige Qi; Yutong Zhou; Qingjie Li; Minda Liu; Na Hu; Jianfeng Wang; Jiazhang Qiu; Xuming Deng; Lei Xu (Veterinary Research)
Abstract Pullorum disease, caused by Salmonella pullorum (S. pullorum), is a highly contagious illness affecting the poultry industry. Emerging evidence suggests that Artemisia argyit essential oil can influence the composition of gut microbes in the host, thereby promoting overall health. However, the specific mechanisms by which Artemisia argyit essential oil modulates gut microbiota to combat S. pullorum infection remains unclear. This study explored the effectiveness of various doses of Artemisia argyit essential oil in preventing S. pullorum infection in chicks. Our findings indicate that consuming this essential oil can mitigate the intestinal mucosal barrier damage and excessive inflammatory response caused by S. pullorum, as well as reverse the weight loss seen in infected chicks. Additionally, chicks that received faecal microbiota transplantation (FMT) from the gut microbiota of Artemisia argyit essential oil donors exhibited notable recovery from S. pullorum infections. This suggests that the observed protection may be linked to the modulation of gut microbiota. Furthermore, 16S rRNA sequencing revealed an increased abundance of Lactobacillus reuteri (L. reuteri), which along with the activation of Wnt/β-catenin pathways, played critical roles in the enhanced health of S. pullorum-infected chicks treated with Artemisia argyit essential oil. In summary, these findings highlight that the dietary inclusion of Artemisia argyit essential oil promotes the intestinal enrichment of L. reuteri, offering a promising strategy for the treatment and prevention of pullorum disease in chicks.